2018
DOI: 10.1136/bmjgh-2017-000571
|View full text |Cite
|
Sign up to set email alerts
|

Estimated costs of production and potential prices for the WHO Essential Medicines List

Abstract: IntroductionThere are persistent gaps in access to affordable medicines. The WHO Model List of Essential Medicines (EML) includes medicines considered necessary for functional health systems.MethodsA generic price estimation formula was developed by reviewing published analyses of cost of production for medicines and assuming manufacture in India, which included costs of formulation, packaging, taxation and a 10% profit margin. Data on per-kilogram prices of active pharmaceutical ingredient exported from India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 14 publications
1
60
0
4
Order By: Relevance
“…The current price for rifabutin per 150 mg tablet is $0.94 . Estimated generic prices for rifabutin regimens were calculated using a previously validated cost estimation algorithm . Per‐kilogram price of active pharmaceutical ingredient exported from India was collected from the http://www.infodriveindia.com database.…”
Section: Cost Considerationsmentioning
confidence: 99%
“…The current price for rifabutin per 150 mg tablet is $0.94 . Estimated generic prices for rifabutin regimens were calculated using a previously validated cost estimation algorithm . Per‐kilogram price of active pharmaceutical ingredient exported from India was collected from the http://www.infodriveindia.com database.…”
Section: Cost Considerationsmentioning
confidence: 99%
“…Growth in off-patent pharmaceutical prices is also worrying. For example, a recent analysis found that most of the medicines on the WHO essential medicines list are sold in the UK and South Africa at prices significantly higher than those estimated from production costs; some generic medicines are priced at more than 100 times their estimated cost of production 27. Such prices suggest that market power is being exercised in ways inconsistent with the notion that off-patent pharmaceuticals should be available at prices close to the cost of production—the hallmark of ideal economic markets characterised by truly competitive pricing.…”
Section: Concerning Trendsmentioning
confidence: 99%
“…Data on manufacturing costs are not usually made public. Costs may be discovered, however, by prices under competitive market conditions or estimated by experts using prices of inputs 1516. Medicines have considerable economies of scale, and predictability of orders and payment enables suppliers to manufacture efficiently.…”
Section: Fairness To Sellersmentioning
confidence: 99%